A review of market prices of selected commodities and services: Imo State 1978 - Federal Ministry of Financial and Economic Development (Owerri: Federal Ministry of Financial and Economic Development, 1978)
This publication is the review of the 1978 market prices of selected commodities and services. It provides information on those commodities and services that are regularly bought and used by households in the six urban centres covered.
rpm 01/02/2019
Loans
Keywords: Market Prices; Imo State